Prolonged QT in a 13‐Year‐Old Patient with Down Syndrome and Complete Atrioventricular Canal Defect - Tisma‐Dupanovic, Svjetlana (Ann Noninvasive Electrocardiol, 2011)
Ann Noninvasive Electrocardiol 2011;16(4):403–406